2013
DOI: 10.1111/ajt.12411
|View full text |Cite
|
Sign up to set email alerts
|

Living Kidney Donor Assessment: Challenges, Uncertainties and Controversies Among Transplant Nephrologists and Surgeons

Abstract: The assessment of living kidney donors presents unique ethical challenges and complex psychosocial implications. This study aimed to ascertain the perspectives of transplant nephrologists and surgeons on living kidney donor assessment. Semi‐structured, face‐to‐face interviews were conducted with 110 transplant nephrologists and surgeons from 43 transplant units in 12 countries from Europe, Australasia and North America. The challenge of defining acceptable risk to the donor was central to five themes identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…20,21 This may represent a response that is highly influenced by the psychological benefits of donation. 22,23 The finding illustrates the important interplay between patient characteristics and individual domains of pain perception. This observation argues against opinion that the only way to improve pain management is the strict use of protocols for monitoring and administering analgesics.…”
Section: Discussionmentioning
confidence: 77%
“…20,21 This may represent a response that is highly influenced by the psychological benefits of donation. 22,23 The finding illustrates the important interplay between patient characteristics and individual domains of pain perception. This observation argues against opinion that the only way to improve pain management is the strict use of protocols for monitoring and administering analgesics.…”
Section: Discussionmentioning
confidence: 77%
“…The qualitative literature has addressed donor psychosocial outcomes in considerable detail, due to the very nature of how these studies are conducted and the types of data they generate. Studies have focussed on many different aspects, such as decision‐making, expectations and the opinions of transplant professionals . They have also identified concerns regarding donor mental health and whether the benefits of donation outweigh the risks .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, there is not much research on attitudinal differences between nephrologists and surgeons (30). Rather, most studies focus on variability between renal transplant programs and offered little insight into similarities and differences between surgeon respondents and nephrologist respondents (12,31,32). We found that surgeons and nephrologists had strikingly similar views.…”
Section: Discussionmentioning
confidence: 99%